Analisis Faktor-Faktor Psikologis Yang Mempengaruhi Keputusan Konsumen: Pendekatan Data Mining Menggunakan Rapidminer - Uhti Lestar; Anna Dina Kalifia (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
Literary psychology is a branch of psychology that studies the interaction between psychology and literature. It involves analyzing and understanding how psychological elements, such as emotion, motivation, perception, and personality, can be understood through literary works. Literary psychology tries to explain and understand human experiences expressed in literary works, as well as how literary works can influence and affect readers emotionally and psychologically. "Analysis of Psychological Factors that Influence Consumer Decisions in Choosing the Modern Market: Data Mining Approach using RapidMiner" - Research This aims to find out which psychological factors influence consumer decisions in choosing modern markets. The type of research carried out is explanatory research which explains the causal relationship between variables through hypothesis testing. In this research, analysis of the coefficient of determination is carried out to determine consumer psychological factors. which contributed 62.1% in influencing purchasing decisions, while the remaining 37.9% was influenced by other factors in analysis using the Decision Tree method: This method is used to build prediction models based on decision trees. Decision trees can help identify the psychological factors that are most influential in making consumer decisions.